Manajemen Pembelajaran Berbasis Integrasi Agama dan Sains Dalam Penguatan Kompetensi Profesional Calon Pendidik di LPTK Muhammadiyah - Ahmad Suryadi; Akhmad Shunhaji; Ahmad Zain Sarnoto (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
While the concept of integrating religion and science is frequently debated at philosophical and epistemological levels, there remains a critical need to operationalize these ideas into concrete learning practices within Islamic educational institutions. This research investigates the technical policies guiding the management of this integration through the Al-Islam and Kemuhammadiyahan (AIK) curriculum at the Faculty of Education, University of Muhammadiyah Jakarta. Utilizing a qualitative-descriptive approach structured around a case study method, the study reveals that the integration of religious values and scientific inquiry is systematically applied across AIK courses 1 through 4. Specifically, the AIK-3 course focuses on "Muamalah and Islam as a Discipline of Science," successfully blending religious doctrine with educational theory. Practical implementation includes initiating lectures with Quranic recitation, explicitly linking verses to academic course material, requiring religious evidence in research theses, and fostering Islamic conduct on campus. The AIK course serves as a model of integration and a platform for character and spiritual development in FIP graduates as future professional educators with a vision to eliminate the dichotomy between science and religion. Muhammadiyah educational institutions and integrated Islamic school also require teachers to manage integrated learning between science and religion concepts holistically.ABSTRAKGagasan integrasi masih berada di aras pemikiran para filosof dan epistemologi sehingga perlu di implementasikan dalam praktik pembelajaran di lembaga pendidikan Islam. Penelitian ini bertujuan mengkaji kebijakan teknis penerapan manajemen pembelajaran berbasis integrasi agama dan sains melalui Mata Kuliah Al-Islam dan Kemuhammadiyahan (AIK) di Fakultas Ilmu Pendidikan, Universitas Muhammadiyah Jakarta. Penelitian menggunakan pendekatan kualitatif-deskriptif dengan metode studi kasus. Hasil penelitian ini menunjukkan bahwa manajemen pembelajaran berbasis integrasi agama dan sains diterapkan pada Mata Kuliah AIK mulai dari AIK 1 sampai 4. Khusus pada AIK-3 dibahas tema Muammalah dan Islam Disiplin Ilmu yang banyak mengintegrasi konsep ilmu agama dan ilmu pendidikan dalam bentuk tadarus Al-Qur’an sebelum perkuliahan, mengaitkan ayat al-Qur’an dengan materi kuliah Ilmu Pendidikan, pencantuman ayat dan dalil pada skripsi, penerapan perilaku Islami di kampus. Mata Kuliah AIK menjadi model integrasi dan wadah pembentukan karakter dan jiwa lulusan FIP sebagai calon pendidik profesional yang memiliki visi untuk menghilangkan dikotomi sains dan agama. Lembaga pendidikan Muhammadiyah dan Sekolah Islam Terpadu juga menuntut kemampuan guru untuk mengelola pembelajaran integratif antara konsep sains dan agama secara utuh.